Structural Model Of The Relationships Between Perceived University Climate Quality, Academic Subjective Well-Being, And Citizenship Values Among King Khalid University Students - Ibrahim, Asem M.; Abbady, Adel S.; Abdelmagid, Ahmed S.; Alim, Eismat F. Abdel (Migration Letters, 2024)
This research aimed to reveal the relationships between the Perceived University Climate Quality (PUCQ), Academic Subjective Well-being (ASW), and Citizenship Values (CV) among King Khalid University (KKU) students, and to build a model that explains these relationships. The descriptive approach was used. A scale of the PUCQ, a scale of ASW, and a scale of CV for university students were prepared and adapted. The research sample consisted of 134 male and female KKU students. The results were processed using SPSS and AMOS.25. The results revealed the presence of positive and statistically significant correlations at the level (0.01) between the PUCQ, ASW, and CV among the research sample. A structural model was presented that explains the modeling of the mutual relationships between the PUCQ, ASW, and CV among university students. The standard value of χ2 was 1.18, which is not statistically significant.